How Does the Implicit Awareness of Consumers Influence the Effectiveness of Public Service Announcements? A Functional Near-Infrared Spectroscopy Study - Fu, Jialin; Li, Xihang; Zhao, Xi; Zhang, Keyi; Cui, Nan (Frontiers in Psychology, 2022)
A large number of scholars have conducted detailed studies on the effect of commercial advertising on individuals by using neuromarketing methods; however, few scholars have paid attention to the effect of public service advertisements (PSAs) on individuals. To research the relationship between the effect of PSAs and the audience's implicit awareness, this study employed functional near-infrared spectroscopy (fNIRS) to record the neural activity data of 30 participants while they watched agricultural PSAs. The results of the study showed that there was a correlation between participants' purchase intention of agricultural products in PSAs and participants’ neural responses. Moreover, the activation degree of the dorsolateral prefrontal cortex (dlPFC) could be used as an indicator to improve the advertising effect. In addition, this study provided a new method for the study of the effect of PSAs.